Supply Chain Governance, Corporate Governance and Supply Chain Capabilities: An Unexplored Nexus - Brahmana, Sunardi; Hendar, Hendar; Mu’minah, Iin; Ahmad Razimi, Mohd Shahril Bin (ExcelingTech, 2019)
Supply Chain governance is an emerging phenomenon, the interorganizational theories are placing an increasing emphasis on the internal governance, which helps a firm in integrating the process and networks by keeping or sustaining theory dynamic nature. The prime objective of the current study is to explore the impact of supply chain governance on supply chain capabilities. Meanwhile the study has examined the mediating role of corporate governance in the relation between the supply chain governance and supply chain capabilities. We have used the SEM-PLS as a statistical tool to achieve the objectives of the current study. The data is collected with the aid of an adapted questionnaire. The operation managers and finance managers of Indonesian manufacturing firms are chosen as final sample of the current study. The results of the study are providing support to the proposition of agency theory and resource-based theory. Overall the findings of the current study are in line with the proposed findings.